(untitled) (Research, Society and Development, 2021)
The small producer is present in the context of agricultural production that sustains Brazil, and suffers the first impacts of these synthetic substances used in the maintenance of crops, which was the motivation to propose the present study. The general objective of this study was to examine the use of pesticides in the municipalities of Miguel Pereira and Paty do Alferes, as well as to evaluate the disposal of packaging through analysis carried out with focus groups. From the study, it was noticed a correlation between producer education and correct handling and less harmful pesticides. Some producers exposed the need for diversification of crops for the survival of their properties, in view of the impossibility of acquiring increasing doses of pesticides for the cultivation of tomatoes. However, without proper technical guidance, they did not realize the possibility of contamination of the aquifer by the use of pesticides, are subject to diseases of the central nervous system and can bioaccumulate contaminants.